Audit of catheter urine culture requests. Issue 1 (January 1992) - Manek, N; Napier Rees, E
Abstract : An audit to assess the appropriateness of catheter urine culture requests was carried out for a period of one month. The requests were followed up by members of the Infection Control Team at ward level. The laboratory report had no impact on the removal of the catheter in asymptomatic or symptomatic patients, although the reports did aid antibiotic prescribing in symptomatic patients.